Intravaginal boric acid: is it an alternative therapeutic option for vaginal trichomoniasis?. (9th December 2017) - Thorley, Nicola; Ross, Jonathan
Abstract : Objectives: Trichomoniasis, caused by Trichomonas vaginalis (TV), is the most common curable sexually transmitted infection worldwide. Current guidance in the UK is to treat TV with a nitroimidazole antibiotic. The high prevalence of TV, high rate of antibiotic resistance and limited tolerability to nitroimidazoles suggest that alternative treatment regimens are needed. Intravaginal boric acid (BA) has been used safely for the treatment of candida vulvovaginitis and bacterial vaginosis, and in vitro studies suggest BA is active against TV. We review the evidence for the efficacy of BA in patients with TV. Methods: MEDLINE, EMBASE, CINAHL, AMED, HMIC and BNI and Grey literature databases, The Cochrane Library, Trial Registers, conference abstracts and proceedings were searched. Inclusion criteria were women aged 16 years or over with microbiological confirmation of TV infection and using BA as treatment. There were no restrictions on language, publication date or study design. The in vitro evidence for BA activity against TV was also reviewed. Results: No randomised controlled trials or case series were found. Four case reports demonstrated TV clearance with BA using a variety of dose regimens (dose 600 mg alternate nights to 600 mg two times per day; duration 1–5 months). In vitro studies suggest that BA has activity against TV which is independent of its effect on pH. Discussion: Further evaluation of BA for the treatment of uncomplicated TV is required, but it may be useful when therapeutic options are limited. If shown to be safe and effective, intravaginal BA might provide a well-tolerated alternative anti-infective treatment which reduces community exposure to systemic antibiotics.